Movement from Object Position in Chinese: a Restriction on Substitution - Lu, Zhong-ying (Linguistica Atlantica, 1995)
There is a subject-object asymmetry in Chinese, such that the extraction of a possessor NP from a possessive NP is quite free from subject position but restricted from object position. A possessive tJP consists of a possessor NP which is the modifier, and a possessed NP that is the head, usually remaining in the subject or object position. When a possessive NP functions as subject in a simple sentence, the possessor NP can always be extracted to clause-initial position to act as a new topic of the sentence, but only a few possessor NPs can be extracted from object position. This article analyzes the substitutability of NPs in subject and object position, concluding that where there is a restriction on NP movement from object position, this is essentially caused by a semantic contradiction possibly created during the movement. Based on a hierarchy of NP subcategories, 9-roles, and possessive relations, this paper also develops two generalizations to stipulate the necessary conditions for the movement of relevant NPs from object position. This work may therefore help provide an explanation for subject-object asymmetry in Chinese.